2018
DOI: 10.1038/s41598-018-19572-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anemia in colorectal cancer: relationships with tumor characteristics, systemic inflammation, and survival

Abstract: Anemia is common in colorectal cancer (CRC) but its relationships with tumor characteristics, systemic inflammation, and survival have not been well characterized. In this study, blood hemoglobin levels and erythrocyte mean corpuscular volume (MCV) levels were measured in two independent cohorts of 148 CRC patients and 208 CRC patients, and their correlation with patient and tumor characteristics, systemic inflammatory markers (modified Glasgow Prognostic Score: mGPS; serum levels of thirteen cytokines, C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 53 publications
10
109
3
2
Order By: Relevance
“…Since these serum marker combinations may explain why anaemia is associated with poor patient outcomes, we evaluated the association between anaemia and PNI (calculated from serum total lymphocyte count and albumin) and mGPS (scored from serum albumin and CRP), which reportedly predict cancer patient outcomes. A few studies have reported that anaemia is more common in CRC patients with increased mGPS . However, to our knowledge, this is the first report of PNI as an anaemia‐related prognostic marker for CRC.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Since these serum marker combinations may explain why anaemia is associated with poor patient outcomes, we evaluated the association between anaemia and PNI (calculated from serum total lymphocyte count and albumin) and mGPS (scored from serum albumin and CRP), which reportedly predict cancer patient outcomes. A few studies have reported that anaemia is more common in CRC patients with increased mGPS . However, to our knowledge, this is the first report of PNI as an anaemia‐related prognostic marker for CRC.…”
Section: Discussionmentioning
confidence: 72%
“…Väyrynen et al . also showed that BRAF mutation and high microsatellite instability status, key right‐sided CRC features, had no significant association with anaemia. However, the fact that anaemia is strongly associated with right‐sided CRC highlights the utility of an immunological viewpoint when considering CRC patients with anaemia.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations